Potencial da biomassa de microalgas dulcícolas na proteção de culturas probióticas durante liofilização e armazenamento - Mafaldo, Ísis Meireles (2022)
Freeze drying is a method most used for the conservation of probiotic cultures. However, cell damage resulting from the process may compromise probiotic viability. The use of mono-, di-, and polysaccharides that prevent cell membrane disruption and protect probiotic cells can reduce damage during freeze dried. Freshwater microalgae contain in their composition non-digestible polysaccharides that can exert such protection. The aim of this study was to evaluate the potential of the microalgal biomass Chlorella vulgaris (CV), Spirulina platensis (SP), Lagerheimia longiseta (LL) and Scenedesmus quadricauda (SQ) as protective agents of probiotic cultures [Lactobacillus acidophilus 5 (La-5) e Lacticaseibacillus casei 1 (Lc-1)] during freeze drying, refrigerated storage (0, 7, 15, 30, 60, 90 and 120 days at 4 ºC) and simulated gastrointestinal conditions (SGIC). The membrane integrity was evaluated in a flow cytometer using propidium iodide and the ultrastructural aspects of the freeze-dried cells were evaluated using a scanning electron microscope. Fructooligosaccharides (FOS) and saline (SS) were used as positive and negative controls, respectively. A reduction of 1-2 log CFU/g (p < 0.05) was observed after freeze drying of the cultures, with a protective effect on biomass varying between probiotic strains and microalgae species. All microalgae biomass showed a protective effect during long refrigerated storage, of 90 and 120 days for La-5 and Lc-1, respectively. After 120 days of refrigerated storage, SP biomass showed the highest probiotic counts for La-5 (9.81 log CFU/g) while for Lc-1 the highest counts were observed for the freeze-dried culture with SQ (9.08 log CFU/g). g) and FOS (9.33 log CFU/g) (p < 0.05). The probiotic La-5 was more resistant to refrigerated storage than Lc-01 (p < 0.05; reduction of 1.1 vs 2.65 log CFU/g). All freeze-dried microalgae biomasses with both probiotic cultures provided counts greater than 6.15 log CFU/g after in vitro digestion. The survival of probiotics to in vitro digestion was dependent on the strain and microalgae used, however the highest count was observed for the Lc-1 strain freeze dried with CV (7.3 log CFU/g). The use of SP, CV, LL biomass resulted in less membrane damage (12.5 to 59.2%) compared to FOS (53.9 to 61.3%) for both probiotic cultures (p < 0.05). The micrographs showed the adhesion of La-5 and Lc-1 to the microalgae, in addition to the formation of exopolysaccharides for both strains freeze dried with LL. The results show the potential of the application of freshwater microalgae biomass as protectors of probiotic cultures, especially for CV and SP.